Arbitration for the resolution of administrative disputes: evolution or revolution? - Esplugues Barona, Carla (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The 21st century dawns with social changes and the transformation of the administrative structures. These changes affect the relations between the Administration and the citizens and lead to the search for new ways of solving their problems. Despite the existing allure for the so called Alternative Dispute Resolution or ADR, Administrative law remains a field full of obstacles to their incorporation.
Keywords: arbitration; ADR; Administrative Law